Sorties from the Fortress: The Current System of Anti-Immigration Policy in Germany - Ralph Rotte (Institute for the Study of Labor (IZA), 1998)
This paper gives a short synoptical overview of the most important elements of current anti-immigration policy in Germany. Based on the hypothesis that its primary aim is exclusion of new migrants, the measures taken within the framework of a groupwise nationally oriented but internationally cooperative approach are summarized. It is argued that German migration policy constitutes a complex system in which one has to take account of administrative and legal measures, as well as of applied instruments of foreign policy and development assistance. It should therefore not be characterized as a strictly defensive ?Fortress Germany? approach any more.
Keywords: H77; F22; K30; 330; immigration policy; international cooperation; Migrationspolitik; Deutschland